Determinants of Muslim Entrepreneurs Decisions On Sharia Bank Financing and Its Effect On Business Performance - Alimusa, La Ode (Universitas Islam Negeri Raden Intan Lampung, 2019)
The purpose of this study is to determine the factors that influence the decisions of Muslim entrepreneurs in using Islamic bank financing products and their influence on Business performance in MSMEs. The variables studied were religious factors, service quality, accessibility, reference groups, promotions, profit sharing systems and attitudes towards fatwas. The research method used is the factor analysis method (Exploratory Factor Analysis) and multiple linear regression. sampling technique is non-probability sampling (incidental sampling) that is equal to 70 people with assumptions considered sufficient to represent the population, while the method of collecting data through questionnaires.The results showed thatthere are 2 (two) main factors that determine the behavior of entrepreneurs in using Islamic bank financing, namely external drives (promotion, accessibility, reference groups, and attitudes to the bank system), and internal references (religion, service quality, and profit sharing system). Profit sharing system is the most important factor for customers in deciding to use Islamic bank financing products. The factors of using these financing products have a significanth effect on the performance of small and medium enterprises (SMEs) in Southeast Sulawesi, IndonesiaKeywords : Muslim Entrepreneurs, Sharia Banks and Business